Two new species in the Anthaxia (Anthaxia) manca (Linnaeus, 1767) species-group from China (Coleoptera: Buprestidae) - Bílý, Svatopluk (Zootaxa, 2005)
Two new species in the Anthaxia (Anthaxia) manca (Linnaeus, 1767) species-group: Anthaxia (Anthaxia) ulmi new species and A. (A.) cupressi new species, from southern China, are described, illustrated and compared with related species. Short comments on the taxonomic history, distribution and bionomy of the group are given.